Cytosolic components of the respiratory burst oxidase: resolution of four components, two of which are missing in complementing types of chronic granulomatous disease. - Curnutte, J T (1989)
The respiratory burst oxidase of neutrophils can be activated in a cell-free system in which plasma membranes, cytosol, Mg2+, and a membrane-perturbing detergent, such as arachidonate or sodium dodecyl sulfate, are all required. Using the technique of preparative isoelectric focusing, the cytosol factor required for oxidase activation was resolved into four components termed C1-C4 with respective pI values of approximately 3.1, 6.0, 7.0, and 9.5. Individually, these components were incapable of activating the oxidase and could only be detected in the presence of suboptimal amounts of normal cytosol that served to supply at least a limited amount of each of the required components. Attempts to activate the oxidase with a combination of the four components failed, suggesting that there might be a yet undetected fifth cytosolic component. Patients with autosomal recessive cytochrome b-positive chronic granulomatous disease (type II CGD) are severely deficient in cytosol factor activity. When added to cytosol samples from two patients with this form of CGD, component C4 restored the ability of each patient's cytosol to activate dormant oxidase. None of the other three cytosol factor components (C1-C3) was effective in this regard, a finding supported by the direct demonstration that these three components were present in normal amounts in this type of CGD. A different form of type II CGD was identified in a third patient on the basis of complementation studies in which the patient's cytosol was able to activate the oxidase in the cell-free system when mixed with cytosol from one of the first two patients. The defect in this third patient's cytosol could be partially corrected by component C2, but not component C4, obtained from normal cytosol. These findings indicate that the role of cytosol in the activation of the respiratory burst oxidase is more complex than previously appreciated in that at least four cytosolic components appear to be required. Defects in two of these components have now been identified and appear to be responsible for two biochemically distinct forms of CGD.